They Are Leaving, They Are Leaving… - Smirnova, Olga (project baikal, 2019)
The author describes how people leave Krasnoyarsk and move to other regions. The author attributes the migration from Siberia to the bad ecological situation in the region. The author points out that the health values prevail over the career values and radically define the life choice.